THE MECHANISM OF CONTRADICTIONS IN THE CONTEXT OF MANAGING SOCIAL CONFLICTS IN PUBLIC POWER - STADNIYCHUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the mechanism of contradictions in the context of managing social conflicts in public power. Chronic disagreements have been found to be seen as a serious source of conflict in the workplace, and in most cases they relate to structures, systems, processes, stereotypes, bureaucratic organization, and bad relationships, as well as ways to encourage, evaluate, and give value to work. Social conflicts are recognized by: repetition of claims; low level of attachment; tolerance for antagonism; low level of their resolution; high intensity of emotions that they cause. Other key contradictions of tension and conflict can be found in how managers perceive and perform their role. This tension was characterized and mainly related to the alleged psychological contract between employees and employers. What is known as abusive supervision of subordinates can take many forms, such as: verbal or nonverbal violence, favoritism, Gossip; mobbing: subversion; unfair, subjective, and unjustified distribution of responsibilities.; expression of irony; discrimination, religious, political or philosophical beliefs; invasion of privacy; reallocation of responsibilities in case of violation from the upper to the lower hierarchical levels; poor assessment of employees ’ work. Prevention and resolution of social conflicts refers to a wide range of practices and methods aimed at reducing the likelihood of conflict and, if a conflict occurs, developing effective solutions to these conflict situations. Conflict prevention and resolution can often be most effective with the help of unbiased third parties, such as a mediator or mediator. Therefore, there is an urgent need to propose a serious attitude to the mechanism of contradictions in the context of managing social conflicts in public authorities, since they can harm the activities of the organization and the economy and society as a whole. Conflict management and misdeeds in public authorities or administrations deserve the involvement of researchers who could offer adequate solutions and facilitate the implementation of ongoing reforms. In addition, social conflicts, which manifest themselves especially in the public sector, deserve careful study, since they have specific characteristics.